(untitled) (Global Journal of Human-Social Science, 2023)
Moreover we know that all things work together for good to them that love God to them who are the called according to his purpose Romans 8 28 King James I pray that whoever this book will understand that God our Father has a place for you and a plan I hope the journeys you travel will bring you joy I pray that you find your purpose that God has for you and that you take on that calling This book is dedicated to my mother Mary M Graham Davenport who set a Christian foundation her walk with Christ led me to become a Christian first then a preacher